Sobre rosas e espinhos - experiências de trabalho com flores na região de Holambra (SP) - Bueno, Juliana Dourado (Universidade Federal de São Carlos, 2016)
This thesis aims to analyze the contradictions present in the cultivation of flowers, highlighting the life experiences of men and women working in the fields and greenhouses of flowers in the region of Holambra, São Paulo, Brazil. The theoretical references are the studies on rural wage and on the globalized intensive agricultural. The field research was conducted in four cities: Artur Nogueira, Holambra, Mogi Mirim and Santo Antônio de Posse. The narratives were collected through conversations and interviews at workers home. The methodology used was the Oral History, which allowed us to view the work in addition to the data brought by the official statistics, trying to break with the analyzes that polarize the productive and reproductive spaces, and naturalize the female skills. The research has allowed us to verify the existence of a variety of settings that make the work morphology in growing flowers - this diversity relates to the size of the properties and greenhouses, forms of employment (family labor, wage, unregistered work), and the place of residence of workers (rural districts, urban districts, producing colonies of flowers). People interviewed related that the working hours are intensified to fulfill the demands, there is exposure to pesticides and thorns of flowers, and carrying out the activity in the greenhouses and fields is often strenuous, which makes some people use medicines to face the workload. Finally, we present a discussion on ways of estrangement and the possibilities of creating emotional bonds with the plants, which causes the activity to be evaluated positively by workers.
Keywords: Trabalho rural; Cultivo de flores; Região de holambra/SP; Relações sociais de classe e gênero; Rural labor; Cultivation of flowers; Region of Holambra / SP; Social relations of class and gender; CIENCIAS HUMANAS::SOCIOLOGIA